Chiroptical Properties of Carbo[6]Helicene Derivatives Bearing Extended π‐Conjugated Cyano Substituents. Issue 8 (17th July 2013) - Moussa, Mehdi El Sayed; Srebro, Monika; Anger, Emmanuel; Vanthuyne, Nicolas; Roussel, Christian; Lescop, Christophe; Autschbach, Jochen; Crassous, Jeanne
ABSTRACT New carbo[6]helicene derivatives grafted with π‐conjugated cyano‐phenyl arms were synthesized in enantiopure forms and their π‐conjugation examined by UV–vis spectroscopy. The influence of the π‐conjugation on the circular dichroism spectra and molar rotations is discussed based on comparing experimental data with results from quantum‐chemical calculations. The results highlight the fact that increasing the spatial extension of the π‐system in a helicene molecule is an efficient way of increasing its molar rotation. Chirality 25:455–465, 2013. © 2013 Wiley Periodicals, Inc.